153k views
0 votes
Solve. Show your work.log3 (2x + 1) = log3 (6x – 23)

User Cokegod
by
6.1k points

1 Answer

2 votes

Answer:


x=6

Step-by-step explanation:

To solve this, we need to use two properties of logarithms.

The first one is the difference of logarithms with same base:


\log_a(x)-\log_a(y)=\log_a((x)/(y))

The second one is the definition of logarithm:


\log_aN=x\Leftrightarrow N=a^x

Then, we are given the equation:


\log_3(2x+1)=\log_3(6x-23)

Then:


\operatorname{\log}_3(2x+1)-\operatorname{\log}_3(6x-23)=0

Applying the first property, for difference of logs:


\operatorname{\log}_3((2x+1)/(6x-23))=0

Now we apply the definition of log:


\log_3((2x+1)/(6x-23))=0\Leftrightarrow(2x+1)/(6x-23)=3^0

And now we can solve as any rational equation:


\begin{gathered} (2x+1)/(6x-23)=3^0 \\ . \\ (2x+1)/(6x-23)=1 \\ . \\ 2x+1=1(6x-23) \\ 2x+1=6x-23 \\ 1+23=6x-2x \\ 24=4x \\ . \\ x=(24)/(4)=6 \end{gathered}

Thus, the answer is x = 6

User Cozimetzer
by
5.9k points